The Role of Parents in the Age of Information Technology for Early Childhood - Ali Afrizal; Siti Nur Ajizah (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
Parents have the most influence on the success of a child's development. However, many parents do not realize how important the role of parents is in shaping the personality of their children, especially in the era of information technology. Many parents fully entrust their children's education to school institutions without any good synergy between educational institutions and parents in children's education. Communication technology can bring both opportunities and distance to the relationship between parents and the environment with children. The challenge for parents to play an active role in improving the quality of education for early childhood in particular, because parents are the closest people to children. The existence of technology does not mean that children are given the freedom to enjoy all the technological facilities available, but they should be able to utilize technology to improve children's self-quality and prepare strong generations based on families.Keywords: Role, Parents, Information Technology Era, Early Childhood